2023
DOI: 10.1021/acssuschemeng.2c05539
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Stackable CO2-to-CO Electrolyzer Cell Design─Impact of Media Flow Optimization

Abstract: Aqueous CO 2 -to-CO electrolysis is a promising technology for closing the carbon cycle and defossilizing industrial processes. Considering the technological readiness, consensus has been achieved about using silver as a stable and selective electrocatalyst for the CO 2 -to-CO reduction reaction in aqueous electrolyte. On the other hand, challenges such as media flow management, component stability, and force distribution are still associated with improving the process performance and developing a stackable ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…The gas compartment consisted of a titanium flow field with a meandering channel. 18 This flow field also served as the electrical contact for the GDE. A zero-gap counter electrode consisting of an Ir-MMO coated titanium mesh (mesh size: 2 mm × 4 mm, Metakem) was used in the cell.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gas compartment consisted of a titanium flow field with a meandering channel. 18 This flow field also served as the electrical contact for the GDE. A zero-gap counter electrode consisting of an Ir-MMO coated titanium mesh (mesh size: 2 mm × 4 mm, Metakem) was used in the cell.…”
Section: Methodsmentioning
confidence: 99%
“…The authors kindly acknowledge funding by the Federal Ministry of Education and Research (BMBF), Project: iNEW2.0 “Inkubator Nachhaltige Elektrochemie” Funding code: 03SF0627A. The authors thank M. Quentmeier for designing the titanium flow frame, 18 M. Turiaux for supplying gaskets to assemble the GDE flow cell, and A. Luft for his dedicated maintenance of the lab equipment.…”
mentioning
confidence: 99%
“…Moreover, MEA electrolyzers offer the advantage of easy scalability and assembly into stacks, making them highly suitable for industrial applications. 41,42 Janaky et al 43 demonstrated the industrial potential of electrochemical CO production by utilizing commercial silver nanoparticles as catalysts in a multiple electrolyzer stack. The stack was congured with both parallel and serial connections, showcasing the versatility of the system.…”
Section: Performance Indicators Of Meamentioning
confidence: 99%
“…While conductivity is not a significant concern, better thermal conductivity can enhance heat transfer efficiency in the system. Common materials used for the supporting shell include stainless steel and polymer materials such as polytetrafluoroethylene (PTFE) and polyphenylene (PPL) [15] . To ensure high air tightness and prevent leakage and seepage, the surface of the flow cell requires a certain degree of smoothness and excellent corrosion resistance.…”
Section: Selection Of Electrolytic Cell Assemblymentioning
confidence: 99%